Physical Fitness, White Matter Volume and Academic Performance in Children: Findings From the ActiveBrains and FITKids2 Projects - Esteban-Cornejo, Irene; Rodriguez-Ayllon, Maria; Verdejo-Roman, Juan; Cadenas-Sanchez, Cristina; Mora-Gonzalez, Jose; Chaddock-Heyman, Laura; Raine, Lauren B.; Stillman, Chelsea M.; Kramer, Arthur F.; Erickson, Kirk I.; Catena, Andrés; Ortega, Francisco B.; et al. (Frontiers in Psychology, 2019)
Objectives: The aims of this study were (i) to examine the association between cardiorespiratory fitness and white matter volume and test whether those associations differ between normal-weight and overweight/obese children (ii) to analyze the association between other physical fitness components (i.e., motor and muscular) and white matter volume, and (iii) to examine whether the fitness-related associations in white matter volume were related to academic performance. Methods: Data came from two independent projects: ActiveBrains project (n=100; 10.0±1.1 years; 100% overweight/obese; Spain) and FITKids2 project (n=242; 8.6±0.5 years; 36% overweight/obese, United States). Cardiorespiratory fitness was assessed in both projects, and motor and muscular fitness were assessed in the ActiveBrains project. T1-weighted images were acquired with a 3.0 T S Magnetom Tim Trio system. Academic performance was assessed by standardized tests. Results: Cardiorespiratory fitness was associated with greater white matter volume in the ActiveBrain project (P< 0.001, k=177; inferior fronto-opercular gyrus and inferior temporal gyrus) and in the FITKids project (P< 0.001, k=117; inferior temporal gyrus, cingulate gyrus, middle occipital gyrus and fusiform gyrus) among overweight/obese children. However, no associations were found among normal-weight children in the FITKids project. In the ActiveBrains project, motor fitness was related to greater white matter volume (P< 0.001, k=173) in six regions, specifically, insular cortex, caudate, bilateral superior temporal gyrus and bilateral supramarginal gyrus; muscular fitness was associated with greater white matter volumes (P< 0.001, k=191) in two regions, particularly, the bilateral caudate and bilateral cerebellum IX. Six of these regions were related to academic performance, but after correcting for multiple comparisons, only the insular cortex remained significantly related to math calculations skills (=0.258; P<0.005). In both projects, no brain regions showed a statistically significant negative association between any physical fitness component and white matter volume. Conclusions: Cardiorespiratory fitness may positively relate to white matter volume in overweight/obese children, and in turn, academic performance. In addition, motor and muscular fitness may also influence white matter volume coupled with better academic performance. From a public health perspective, implementing exercise interventions that combine aerobic, motor and muscular training to enhance physical fitness may benefit brain development and academic success.